Infoveillance and bibliometric analysis of COVID‐19 in Nigeria - Jimoh Amzat; Kehinde Kazeem Kanmodi; Eyinade Adeduntan Egbedina (Public Health Challenges, 2023)
Abstract Background Infectious diseases often come with enormous fear because of their ability to spark and spread. The same for COVID‐19, which WHO declared a pandemic in February 2020 after a record spread in multiple countries. The global world of information and social media plays a major role in the pandemic. Hence, this study aims to analyse the patterns of internet search and research interests on COVID‐19 in Nigeria. Methods This is an infoveillance and bibliometric research about COVID‐19 in Nigeria using systemic search through Google Trends to obtain COVID‐19 information prevalence and research incidence through bibliometric analysis using SCOPUS database. The data obtained were analysed using the Microsoft Excel 2021 software. Descriptive statistics (frequencies, mean, range and mode) were used for the summarisation of the data. The findings were presented using texts, tables, charts and maps. Results The information search spike started 1 week before the first index case. Search volume index inequalities were observed across the country, with the northern Nigeria having a higher search volume for COVID‐19. This study also uncovered several top search terms, including “COVID‐19,” “COVID loan” and “vaccine,” and queries, including “COVID‐19 Nigeria,” “COVID loan” and “COVID‐19 in Nigeria,” among others, which showed critical infodemiologic concerns in Nigeria. The interests of Nigerian researchers concerning COVID‐19 cut across various disciplines. The top three subject areas with the most significant volume of these publications were Medicine, Social Sciences and Biochemistry. This study found extensive research collaboration with over 150 countries coupled with external funding. Conclusion As internet search spikes reflect population health concerns and information‐wish, understanding the infodemic patterns and search terms will influence mass media regulators and health authorities to be vigilant and tackle the spread of misinformation. Nigeria's research resilience depicts great potential, hence, a call for improved local funding for research and development.